Emcompras.com: elaborando um modelo de negócios para uma plataforma digital de promoções - Klein, Marcelo Bergesch (Universidade do Vale do Rio dos Sinos, 2016)
This monograph will detail the development of a business model for structuring a service that will provide a digital platform focused on gathering, organizing and promoting advertisements for products and services with promotional prices of local individual micro entrepreneurs and micro and small enterprises (MSEs) over the Internet. For this, will be presented information about the Business Model Canvas tool, the profile of MEIs and MSEs, as well as the problems faced by them. Also will be presented studies about the Brazilian consumers profile, on the behavior of generations Y and Z, talent retention, as well as data about the use of the Internet in Brazil and in the world and the main trends and projections. All this study was conducted through research of literature types, documentary and survey, the latter being divided into two parts: a survey and in-depth interview. At the end it will be shown the results of the analysis, listing the issues discussed with the data obtained through the research and presented the preparation of details through the business model canvas tool of a business model in line with the current economic scenario. Thus, the job in question could give support to the development of the business model of other companies who want to start their activities on the Internet or who already do and want to enhance their view on the subject in question.
Keywords: Modelo de negócio para a intenet; Microempreendedores individuais (MEIs); Micro e pequenas empresas (MPEs); Perfil do consumidor brasileiro; Business model for Internet; Micro entrepreneurs; Micro and small enterprises (MSEs); Brazilian customer profile